Signs of Champion: Verbal and Non-Verbal Signs of Liverpool Instagram Post’s - Komang Yoshika Putra; I Wayan Juniartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Aiming to examine how meaning is constructed through visual and textual cues, this research focuses on verbal and non-verbal signs used in selected Liverpool Football Club advertisements posted on Instagram. The objective is to analyze how these elements convey identity, emotion, and cultural resonance in digital football marketing. A qualitative descriptive method was employed, with data consisting of two Instagram advertisements from Liverpool FC’s official account. These posts were chosen based on their prominent use of both linguistic and visual features. Observational techniques were used to identify key verbal elements (slogans, captions, hashtags) and non-verbal components (color, gesture, facial expressions, and composition). The analytical framework draws upon Ferdinand de Saussure’s theory of the signifier and signified, Roland Barthes’ concepts of denotation, connotation, and myth, and Cerrato’s approach to color symbolism in communication. Findings indicate that non-verbal signs hold a more dominant semiotic function, with color especially Liverpool’s iconic red serving as a core emotional and cultural sign. Gestures and facial expressions further amplify the club’s message of pride, unity, and inclusivity. Verbal signs, although fewer in number, play a complementary role by anchoring meaning and enhancing brand recall. Through the combination of both sign types, the advertisements function as complex semiotic texts that engage audiences on both emotional and cultural levels, reinforcing global fan connection and brand identity.